Distribution and the current state of Lagochilus acutilobus (Lamiaceae) in connection with the oil and gas sector development in Uzbekistan - Shomurodov, Habibullo F.; Akhmedov, Akbar; Saribayeva, Shakhnoza U. (Ecological Questions, 2014)
The northern part of the Ustyurt plateau is the main area in Uzbekistan where rare and interesting species Lagochilus acutilobus occurs. The intensified exploration and production of natural gas carried out in recent years by Uzbekistan’s National holding company “Uzbekneftegaz” together with the Russian companies “Lukoil” and “Gazprom” is the main factor degrading the soil and vegetation in this region. Trial drilling, expansion and reconstruction of gas pipelines, as well as the accompanying intensification of transport, cause changes in the distribution and resources of the Lagochilus acutilobus populations. Monitoring of Lagochilus acutilobus was performed in the conditions of strong environmental changes caused by the direct impact of anthropogenic factors enhanced by desiccation of the Aral Sea, the western coast of which bordered previously on the eastern part of the Ustyurt plateau. The species distribution was determined during a series of expeditions in 2011-2013. The maps prepared in the GIS technology show the route and the species occurrence sites located by a GPS receiver. The paper presents the types of plant communities and vegetation complexes in which the studied species occurred. Furthermore, there were determined differences in the abundance of Lagochilus acutilobus in these ecological systems.